PLYOMETRIC EXERCISES AS A WAY OF DEVELOPING SPEED-STRENGHT ABILITIES OF SECONDARY SCHOOL STUDENTS AND POSSIBILITIES OF UTILIZATION IN COEDUCATIONAL LESSONS (Fiep Bulletin - online, 2014)
Physical education and sports as a subject is a place for developing conditional abilities, advancing expansion of general physical performance and fitness. One of the specific aims of this subject is to teach children how to apply and how to plan ways to develop motor abilities in improving their physical performance and fitness, or bring to bear more physical resources to develop their motor abilities. In our report, we will discuss the development of speed-strength abilities of students using plyometric exercises. The aim of our report is to highlight the possibility of using plyometric method to develop speed-strength abilities of secondary school students during physical education within coeducational classes. The contribution is a part of the Ministry of Education’s grant role no.1/0759/12 „Efficiency of coeducational classes of physical education and sport in secondary schools, and its impact on students ‘socialization“. The contribution is a part of the Ministry of Education’s grant role no.1/0759/12 „Efficiency of coeducational classes of physical education and sport in secondary schools, and its impact on students socialization“
Keywords: plyometric exercises; speed-strength abilities; coeducational lessons; secondary school students